Predictors of Functional Outcome After Thrombectomy in Patients With Prestroke Disability in Clinical Practice. Issue 3 (27th October 2021) - Millán, Mònica; Ramos-Pachón, Anna; Dorado, Laura; Bustamante, Alejandro; Hernández-Pérez, María; Rodríguez-Esparragoza, Luís; Gomis, Meritxell; Remollo, Sebastia; Castaño, Carlos; Werner, Mariano; Wenger, Denisse; Rubio, Sara; et al.
Abstract : Supplemental Digital Content is available in the text. Abstract : Background and Purpose: Mechanical thrombectomy (MT) in ischemic stroke patients with poor prestroke conditions remains controversial. We aimed to analyze the frequency of previously disabled patients treated with MT in clinical practice, the safety and clinical response to MT of patients with preexisting disability, and the disabled patient characteristics associated with a better response to MT. Methods: We studied all consecutive patients with anterior circulation occlusion treated with MT from January 2017 to December 2019 included in the Codi Ictus Catalunya registry—a government-mandated, prospective, hospital-based data set. Prestroke disability was defined as modified Rankin Scale score 2 or 3. Functional outcome at 90 days was centrally assessed by a blinded evaluator of the Catalan Stroke Program. Favorable outcome (to return at least to prestroke modified Rankin Scale at 90 days) and safety and secondary outcomes were compared with patients without previous disability. Logistic regression analysis was used to assess the association between prestroke disability and outcomes and to identify a disabled patient profile with favorable outcome after MT. Results: Of 2487 patients included in the study, 409 (17.1%) had prestroke disability (313 modified Rankin Scale score 2 and 96 modified Rankin Scale score 3). After adjustment for covariates, prestroke disability was not associated with a lower chance of achieving favorable outcome at 90 days (24% versus 30%; odds ratio, 0.79 [0.57–1.08]), whereas it was independently associated with a higher risk of symptomatic intracranial hemorrhage (5% versus 3%; odds ratio, 2.04 [1.11–3.72]) and long-term mortality (31% versus 18%; odds ratio, 1.74 [1.27–2.39]) compared with patients without disability. Prestroke disabled patients without diabetes, Alberta Stroke Program Early CT Score >8 and National Institutes of Health Stroke Scale score <17 showed similar safety and outcome results after MT as patients without prestroke disability. Conclusions: Despite a higher mortality and risk of symptomatic intracranial hemorrhage, prestroke-disabled patients return as often as independent patients to their prestroke level of function, especially those nondiabetic patients with favorable early ischemic signs profile. These data support a potential benefit of MT in patients with previous mild or moderate disability after large anterior vessel occlusion stroke.